On Tensor Squares of Reducible Representations of Almost Simple Groups. II - S. V. Polyakov (Моделирование и анализ информационных систем, 2011)
Almost simple SM_m -groups are considered. A group G is called SM_m -group if the tensor square of any irreducible representation is decomposed into the sum of all characters with multiplicities not greater than m. It turned out that if G is an almost simple SM_2 -group, then G congruence PGL_2(q).